Theology of Sagu: A Contextual Theology Construction in Maluku - Rouli Retta Trifena Sinaga (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
After the implementation of rice as a staple food for Indonesian society, including in Maluku, the society of Maluku has become very dependent on rice. Sagu which is a staple and particular food is no longer cultivated and utilized optimally in Maluku. Therefore, through this paper we try to offer theology of sagu, specifically for the Christian society in Maluku. By understanding sagu theologically as a blessing from God that can provide food for society and their harmonious relationship with God, mankind, and nature, this will have implications for the empowerment carried out by The Protestant Church of Maluku on human and natural resources in Maluku. Here the theology of sagu, which is proposed, is constructed from the cosmological view of the Christian society, the biblical basis of John 6:25-59, and some contemporary ecological theological ideas. The purpose of this paper is to add The Protestant Church of Maluku's ecological theology which is being developed to respond to various ecological crises in its context, Maluku. The theology of sagu, which is offered, is to strengthen the church’s Church Teachings, which has been compiled, as the direction of the church’s ministry in the future for its community.